Syngas Underground Coal Gasification (UCG) Testing of In-Situ Type Lignite Coal and Fracture Type Coal - Julismi; Rusdianasari; Abu Hasan (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
The advancement and utilization of technology require energy, namely electricity and fuel energy. The increasing cost of fossil energy, the scarcity of non-renewable energy sources and the increasing energy demand requires diversification of energy resources. One of the new renewable energy sources currently being developed in Indonesia is Underground Coal Gasification (UCG). UCG is a new technology that utilizes unmined coal. In the UCG process, coal is burned underground and the syngas produced is collected through bore wells for processing or direct use. The resulting syngas is analyzed to see the effect of in-situ type of lignite coal and fractured type of coal on syngas production using the UCG method. Tests carried out on fracture-type lignite coal for 120 minutes with a sample weight of 1.3 kg obtained a CH4 gas concentration of 0.24%, which is relatively low compared to the in-situ type lignite coal sample CH4 gas concentration of 1.13%. The CO2 concentration was 54.46% in the fracture sample, and the In-Situ type sample was 52.19%. The O2 content with a value of 19.43% for the Fracture Type sample and 4.94% for the In-Situ type sample. Fracture Type and In-situ Lignite Coal produced fewer syngas products due to UCG testing than high-rank coals such as sub-bituminous and bituminous coal.